Metabolic disturbances in sugar beet (Beta vulgaris) during infection with Beet necrotic yellow vein virus. (December 2020) - Webb, Kimberly M.; Wintermantel, William M.; Wolfe, Lisa; Yao, Linxing; Hladky, Laura Jenkins; Broeckling, Corey D.; Chaves, Fabio Clasen
Abstract: Rhizomania, caused by Beet necrotic yellow vein virus (BNYVV) is an economically important disease of sugar beet. Management includes the use of single resistance ( Rz ) genes. However, strains with the ability to overcome the widely used Rz1 resistance gene have already been reported. The mechanisms associated with these genes are unknown, therefore increased understanding of the host defense response may lead to more durable sources of rhizomania resistance. Non-targeted metabolome profiling, coupled with targeted phytohormone quantification, was applied to characterize the metabolic and signaling pathways associated with BNYVV infections in sugar beet. Clear differences in metabolites were identified following pathogen infection independent of plant genotype particularly those associated with host lipid composition or other membrane associated functions. Highlights: Metabolomics revealed primary and secondary metabolites associated with Beet necrotic yellow vein virus (BNYVV) infection of sugar beet. Differences in metabolite accumulation occurred due to infection with BNYVV irrespective of sugar beet genotype. Content of plant hormones was elevated in BNYVV-infected sugar beets. Specialized metabolites including flavonoids and alkaloids, as well as several lipids had higher accumulation in BNYVV infected plants.